2020
DOI: 10.3390/jcm9093023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Injection of Stromal Vascular Fraction Derived from Autologous Adipose Tissues in Systemic Sclerosis Patients with Hand Disability: A Proof-Of-Concept Trial

Abstract: Background: Stromal vascular fraction (SVF) has recently emerged as a potential therapeutic modality, due to its multipotent cellular components in tissue regeneration. Systemic sclerosis (SSc) is a progressive autoimmune disease that results in hand disability by skin fibrosis and microangiopathies. We performed an open-label study to investigate the efficacy and safety of SVF injection in SSc patients (Clinical Trial number: NCT03060551). Methods: We gathered 20 SSc patients with hand disability, planning fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Interestingly, in one of the cases cells were co-injected with PRP ( Virzì et al, 2017 ). None adverse events were observed, except in two cases where transient paresthesia, pains or pallor in hands were observed ( Granel et al, 2015 ; Guillaume-Jugnot et al, 2015 ; Park Y. et al, 2020 ). Considering effectiveness, those studies with published results demonstrated the benefits of this methodology: Granel et al and Guillaume-Jugnot et al compared the evolution of the disease from the baseline to 12 months after treatment, reporting a significant improvement of 46.8% for the Scleroderma Health Assessment Questionnaire, of 51.3% for the Cochin Hand Function Scale (CHFS) score and of 63.2% for the Raynaud’s Condition score ( Granel et al, 2015 ; Guillaume-Jugnot et al, 2015 ).…”
Section: Mesenchymal Stem Cells In Cutaneous Injuries or Diseasesmentioning
confidence: 92%
See 4 more Smart Citations
“…Interestingly, in one of the cases cells were co-injected with PRP ( Virzì et al, 2017 ). None adverse events were observed, except in two cases where transient paresthesia, pains or pallor in hands were observed ( Granel et al, 2015 ; Guillaume-Jugnot et al, 2015 ; Park Y. et al, 2020 ). Considering effectiveness, those studies with published results demonstrated the benefits of this methodology: Granel et al and Guillaume-Jugnot et al compared the evolution of the disease from the baseline to 12 months after treatment, reporting a significant improvement of 46.8% for the Scleroderma Health Assessment Questionnaire, of 51.3% for the Cochin Hand Function Scale (CHFS) score and of 63.2% for the Raynaud’s Condition score ( Granel et al, 2015 ; Guillaume-Jugnot et al, 2015 ).…”
Section: Mesenchymal Stem Cells In Cutaneous Injuries or Diseasesmentioning
confidence: 92%
“…Ten clinical studies have reported the use of hMSCs as advanced therapy for the treatment of systemic sclerosis in the last 5 years ( Table 9 ; Granel et al, 2015 ; Guillaume-Jugnot et al, 2015 ; Wehbe et al, 2016 ; Song et al, 2017 ; Virzì et al, 2017 ; Zhang et al, 2017 ; Van Rhijn-Brouwer et al, 2018 ; Park Y. et al, 2020 ) (NCT02975960 and NCT04356287). Among these studies, three studies were case reports ( Wehbe et al, 2016 ; Song et al, 2017 ; Virzì et al, 2017 ), in contrast to the rest which were clinical trials.…”
Section: Mesenchymal Stem Cells In Cutaneous Injuries or Diseasesmentioning
confidence: 99%
See 3 more Smart Citations